2011
DOI: 10.1371/journal.pbio.1001149
|View full text |Cite|
|
Sign up to set email alerts
|

Binding of Superantigen Toxins into the CD28 Homodimer Interface Is Essential for Induction of Cytokine Genes That Mediate Lethal Shock

Abstract: Bacterial superantigen toxins bind directly to the dimer interface of CD28, the principal co-stimulatory receptor, to induce a lethal cytokine storm, and peptides that prevent this binding can suppress superantigen lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
244
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(253 citation statements)
references
References 39 publications
8
244
0
1
Order By: Relevance
“…2) inhibited inflammatory cytokine gene expression in human peripheral blood mononuclear cells (PBMC) in the absence of any superantigen, induced by anti-CD28/anti-CD3 monoclonal antibodies, which models the normal T cell-mediated immune response, or by anti-CD28 alone, yet not by anti-CD3 alone [13] . We considered the intriguing possibility that the peptide might compete with the anti-CD28 antibody for its binding site in CD28 and by extension, that the intact superantigen molecule might bind directly to CD28.…”
Section: Cd28 Is An Obligatory Receptor For Superantigensmentioning
confidence: 99%
See 1 more Smart Citation
“…2) inhibited inflammatory cytokine gene expression in human peripheral blood mononuclear cells (PBMC) in the absence of any superantigen, induced by anti-CD28/anti-CD3 monoclonal antibodies, which models the normal T cell-mediated immune response, or by anti-CD28 alone, yet not by anti-CD3 alone [13] . We considered the intriguing possibility that the peptide might compete with the anti-CD28 antibody for its binding site in CD28 and by extension, that the intact superantigen molecule might bind directly to CD28.…”
Section: Cd28 Is An Obligatory Receptor For Superantigensmentioning
confidence: 99%
“…To test this concept, we next screened a random phage display library for peptides that bind to CD28 and are displaced from CD28 by SEB. Indeed, such peptides could be recovered; they strongly inhibited SEB-mediated induction of inflammatory cytokines in human PBMC and protected mice from lethal SEB challenge [13] . Confocal microscopy then showed that labeled SEB colocalizes fully with CD28 expressed on the surface of CD28-transfected cells, providing a strong indication that even in the absence of MHC-II and TCR, the superantigen will bind directly to the extracellular domain of the CD28 receptor [13] .…”
Section: Cd28 Is An Obligatory Receptor For Superantigensmentioning
confidence: 99%
“…These toxins bind directly to the MHC class II molecules on APCs and the variable b-chains of the TCR, and activate the endogenous pathways dependent upon immune synapse formation (12,13). CD28, a costimulatory receptor on T cells, has been recently identified as a superantigen receptor (14). Concerted interaction of the superantigen with all three receptors (CD28, MHC class II, and TCR) allows stable synapse formation resulting in exceptionally robust T cell responses, particularly Th1 cytokine induction, and lethality (14).…”
mentioning
confidence: 99%
“…CD28, a costimulatory receptor on T cells, has been recently identified as a superantigen receptor (14). Concerted interaction of the superantigen with all three receptors (CD28, MHC class II, and TCR) allows stable synapse formation resulting in exceptionally robust T cell responses, particularly Th1 cytokine induction, and lethality (14). Via this mechanism, SEB activates ∼20% of the T cell population, whereas exposure to normal Ags activates ,0.01% of T cells (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation